Botanical Concepts Understanding of Biology Education Students - Khusnul Khotimah; Mucharommah Sartika Ami; Fatikhatun Nikmatus Sholihah (APPLICATION: Applied science in Learning Research, 2023)
This study aims to identify the botanical concepts understanding of biology education students at Universitas KH. A. Wahab Hasbullah. 36 sample students were given a test with two tiers questions (multiple choice with confidence level). The students involved were students who had taken a botany courses. Test results were analyzed descriptive qualitatively. The findings revealed that there were 36,1% of students who understood the concept; 36,1% of students experienced misconception; and 27,8% of students did not understand the concept.   Keywords: Botanical concept; Biology education student; Concept understanding.